2023
DOI: 10.1038/s41598-023-39914-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular-biological features of glioblastoma progression in tolerant and susceptible to hypoxia Wistar rats

Abstract: Hypoxia is a major pathogenetic factor in many cancers. Individual resistance to suboptimal oxygen availability is subject to broad variation and its possible role in tumorigenesis remains underexplored. This study aimed at specific characterization of glioblastoma progression in male tolerant and susceptible to hypoxia Wistar rats. Hypoxia resistance was assessed by gasping time measurement in an 11,500 m altitude-equivalent hypobaric decompression chamber. Based on the outcome, the animals were assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 125 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…High levels of HIF-1α in GBMs have been associated with a poor prognosis and low overall survival [53]. In a recent study, our colleagues reported high mortality in Wistar rats susceptible to hypoxia due to the progression of GBM 101.8 and the larger size of tumors and necrosis areas in rats tolerant to hypoxia [14]. Although we did not observe an upregulation of Hif-1α in any of the three GBM 101.8, GBM 14-4-5, and GBM 11-9-2, the HIF-1α protein content was increased in GBM 101.8 according to WB data.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…High levels of HIF-1α in GBMs have been associated with a poor prognosis and low overall survival [53]. In a recent study, our colleagues reported high mortality in Wistar rats susceptible to hypoxia due to the progression of GBM 101.8 and the larger size of tumors and necrosis areas in rats tolerant to hypoxia [14]. Although we did not observe an upregulation of Hif-1α in any of the three GBM 101.8, GBM 14-4-5, and GBM 11-9-2, the HIF-1α protein content was increased in GBM 101.8 according to WB data.…”
Section: Discussionmentioning
confidence: 97%
“…The GBM 101.8 strain was originally obtained by an intracranial placement of a bolus containing 1 mg of 7,12-Dimethylbenz[a]anthracene (DMBA). It is a particularly aggressive strain, which was used for investigation of chemotherapy for GBM and could be a potentially highly reliable model of human high-grade glioma [13][14][15]. Both GBM 14-4-5 and GBM 11-9-2 strains were obtained from the offspring of rats that were administered an intravenous injection of 75 µg of N-ethyl-N-nitrosourea (ENU) performed on the 20th day of pregnancy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the ECM displays ligands, such as integrins, binding tumor cells and performing mesenchymal migration [33]. Another peculiar feature of GBM is a highly hypoxic TME [34]. Indeed, hypoxia represents a hallmark of GBM, and it is associated with multiple aspects of its pathogenesis (Figure 1) [6,30].…”
Section: Multifaceted Aspects Of Gbmmentioning
confidence: 99%